2017
DOI: 10.3147/jsfp.52.89
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Infection of <i>Renibacterium salmoninarum</i> in Fry and Juveniles Chum Salmon <i>Oncorhynchus keta</i> in Hokkaido, Japan

Abstract: Renibacterium salmoninarum (hereafter referred to as R.s.), the causative agent of bacterial kidney disease (BKD) in salmonids, was detected in the ovarian fluid of returning chum salmon Oncorhynchus keta and masu salmon O. masou propagated in salmon enhancement efforts in Hokkaido, Japan, using nested polymerase chain reaction (nPCR) and quantitative real-time PCR (qPCR) assays for the bacterial genome (specifically, major soluble antigen gene; msa). We detected the R.s. genome in ovarian fluid samples taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In addition, R. salmoninarum has been detected in chum salmon (Oncorhynchus keta) in kidney and mucus samples by Suzuki et al in 2017 in Japan. These authors indicated that R. salmoninarum could be identified from asymptomatic fish in sub-clinical stage of disease by using PCR [21]. Similarly, this organism has been identified in sub-clinical stage in the other different regions and species [53,54].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, R. salmoninarum has been detected in chum salmon (Oncorhynchus keta) in kidney and mucus samples by Suzuki et al in 2017 in Japan. These authors indicated that R. salmoninarum could be identified from asymptomatic fish in sub-clinical stage of disease by using PCR [21]. Similarly, this organism has been identified in sub-clinical stage in the other different regions and species [53,54].…”
Section: Discussionmentioning
confidence: 97%
“…Fish infected with R. salmoninarum can display external and internal clinical signs such as exophthalmia, blebs and blister on the epidermis with white or yellowish haemorrhagic fluid, petechiae and haemorrhages around the fins and lateral line, swelling of the kidney, heart, spleen, and liver alongside creamy-white and greyish granulomatous lesions on the surface of the viscera [18][19][20]. Notably, this organism has been associated with sub-clinical infections in salmonid fish and can establish asymptomatic infections in members of susceptible species [21].…”
Section: Introductionmentioning
confidence: 99%
“…In other recent research, we detected the msa gene DNA and msa mRNA of R. salmoninarum in the kidneys and surface mucus of asymptomatic chum salmon fry and juveniles in a hatchery in Hokkaido (Suzuki et al, 2017). It is well established that R. salmoninarum cells can be transmitted horizontally as well as vertically, from adult females via gametes to offspring (Elliott et al, 1989;Murray et al, 1992;Okuda et al, 2006).…”
Section: Resultsmentioning
confidence: 87%
“…DNA was extracted from samples according to our previous report (Suzuki et al, 2017a). One micro-liter of the DNA solution contained DNA from 1 mg of tissue.…”
Section: Nested Pcr Assay and Quantitative Real-time Pcr Assaymentioning
confidence: 99%
“…One micro-liter of the DNA solution contained DNA from 1 mg of tissue. The nPCR and qPCR assay for the msa gene were conducted as previously reported (Suzuki et al, 2017a). Sensitivity of nPCR was higher than that of qPCR.…”
Section: Nested Pcr Assay and Quantitative Real-time Pcr Assaymentioning
confidence: 99%